Analisis Hasil Belajar Kognitif Siswa Kepribadian Compliance pada Pemecahan Soal Matematika - Prambanan, Didiatma; Dila Yathasya; Anwar, Putri Sakila Amelia (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: The research aims to analyze the results of the study of cognitive student type compliance personality on solving problem mathematics in Theory geometry and knowing what difficulty student inner compliance type solving problem math. Methodology: Method study this is method study qualitative descriptive. Things analyzed in a study results from learning cognitive students and difficulties students on solving material problem trigonometry subject study student compliance personality in class X senior high school PGRI 2, Jambi City. Instruments used in studying this test compliance personality, sheet duty solving problem math, and transcript interview. Main Findings: The result of study is results study cognitive students good compliance personality, but still many there are difficulties in do questions given, seen from the indicator difficulty learning taken, and indicators results in study cognitive students are taken from bloom taxonomy, average yield study cognitive possession student good compliance personality, this show student compliance personality has aspect good cognitive Novelty/Originality of this study: This use analysis results study cognitive students with type compliance personality on solving problem math.